9 - ABDALLA BUJRA’s Legacy in Building the CODESRIA Community - Mshaï Mwangola (CODESRIA Bulletin, 2025)
When the ﬁnal night falls on us as it fell upon our parents, we shall retire to our modest home earth-sure, secure that we have done our duty by our people; we met the challenge of history and were not afraid. With hindsight, from the vantage point of more than half a century on, it is easy to take for granted the legacy that Prof. Abdalla Bujra be- stowed on us as a Council, as a continent and as a community of intellectuals stretching far beyond this continent. For us at CODESRIA, he was one of the (almost mythical at this point) founders, synonymous with the seminal decade of our establishment. His visionary foresight and painstaking labour laid the groundwork for the com- munity we know today. Reﬂecting on the rich treasure trove of historical reminiscences of CODESRIA’s past, delivered during the 50th anniversary celebrations in 2023, I am struck by the immensity and daring of the challenge that he willingly embraced at the behest of Prof. Samir Amin, working closely with colleagues such as Prof. Thandika Mkandawire to build the institution that today is one of the most vibrant and robust African epistemological communities. There is enduring sadness that, with his departure, the Council has closed a chapter in laying to rest the last of the indomitable core crew that worked tirelessly to nurture it into being. However, that grief is tempered with the knowledge of the precious-beyond-words legacy bequeathed to us as a responsibility to hold in trust and pass on to those who will follow.